1994
DOI: 10.1088/0953-8984/6/44/016
|View full text |Cite
|
Sign up to set email alerts
|

Ring exchange and the Heisenberg and Hubbard models

Abstract: We study ring-exchange or cyclic-permutation correlations in one-dimensional quantum spin-half systems. For the Heisenberg model we show numerically that these correlations decay as Rn approximately 1/ square root n, although we can deduce nothing about any possible important logarithmic corrections. As such, ring-exchange correlations are much longer range than the more commonly considered spin-spin correlation functions. By considering the relationship between solitonic excitations and cyclic permutations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In the following we express all energies in units of t 1 = 1 and only consider negative values of t 2 . Because a definite order of the particles is no longer enforced when t 2 = 0, the Lieb-Mattis theorem does not apply and, indeed, ferromagnetism has analytically been shown to exist at U = ∞ in three different limits: For one hole in a half-filled band Nagaoka ferromagnetism has been found [4]; for |t 2 | → 0, it has been shown [5] that the model is ferromagnetic for all densities; and for |t 2 | > 0.25, where the band structure has two minima, Müller-Hartmann [6] has shown that the low density limit is ferromagnetic. These three limits are indicated in the schematic phase diagram shown in Fig.…”
Section: Model and Methodsmentioning
confidence: 99%
“…In the following we express all energies in units of t 1 = 1 and only consider negative values of t 2 . Because a definite order of the particles is no longer enforced when t 2 = 0, the Lieb-Mattis theorem does not apply and, indeed, ferromagnetism has analytically been shown to exist at U = ∞ in three different limits: For one hole in a half-filled band Nagaoka ferromagnetism has been found [4]; for |t 2 | → 0, it has been shown [5] that the model is ferromagnetic for all densities; and for |t 2 | > 0.25, where the band structure has two minima, Müller-Hartmann [6] has shown that the low density limit is ferromagnetic. These three limits are indicated in the schematic phase diagram shown in Fig.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Including a next-nearest-neighbor hopping t 2 , however, ferromagnetism is proven to exist for U = ∞ in the limit t 2 → 0 (t 2 < 0) for all densities. [67][68][69] This limit has to be contrasted to the limit t 1 = 0, but finite t 2 (two-chain model) where the Lieb-Mattis theorem applies again. In the low density limit, the ground state as obtained by the dynamical impurity approximation (DIA, blue).…”
Section: Ferromagnetism In One-dimensional Chainsmentioning
confidence: 99%
“…, N s }, and its hopping amplitudes are defined by t x,x+1 = t x+1,x = −t, t x,x+2 = t x+2,x = t ′ for all x ∈ Λ and t x,y = 0 otherwise. From a first order perturbation theory, it was suggested [66,67] that the model with U = ∞ exhibits ferromagnetism if t ′ > 0. By considering a continuum limit theory, Müller-Hartmann [68] argued that the model exhibits metallic ferromagnetism when 4t ′ > |t| > 0, U = ∞, and the electron density is sufficiently low.…”
Section: Conjectures and Some Evidencementioning
confidence: 99%
“…In a fermion system on a finite lattice, a formal perturbation series alway converges because the operators are finite dimensional. Then one might think that the first order perturbation theories of[66,67,70] imply weak rigorous results that a finite model exhibits ferromagnetism for sufficiently small t ′ /t (or t /t ⊥ ). However, this is not the case since there are no estimates of the energy difference between the ground state and the first excited state, and there remains a possibility that the higher order perturbations change the nature of the ground state for any small values of the expansion parameter.…”
mentioning
confidence: 99%
See 1 more Smart Citation